Cardiomyocyte-specific knockout of ADAM17 alleviates doxorubicin-induced cardiomyopathy via inhibiting TNFα–TRAF3–TAK1–MAPK axis - Lin Xie; Fei Xue; Cheng Cheng; Wenhai Sui; Jie Zhang; Linlin Meng; Yue Lu; Wenjing Xiong; Peili Bu; Feng Xu; Xiao Yu; Bo Xi; et al. (Signal Transduction and Targeted Therapy)
Abstract The pathogenesis of doxorubicin-induced cardiomyopathy remains unclear. This study was carried out to test our hypothesis that ADAM17 aggravates cardiomyocyte apoptosis induced by doxorubicin and inhibition of ADAM17 may ameliorate doxorubicin-induced cardiomyopathy. C57BL/6J mice were intraperitoneally injected with a cumulative dose of doxorubicin to induce cardiomyopathy. Cardiomyocyte-specific ADAM17-knockout (A17α-MHCKO) and ADAM17-overexpressing (AAV9-oeA17) mice were generated. In addition, RNA sequencing of the heart tissues in different mouse groups and in vitro experiments in neonatal rat cardiomyocytes (NRCMs) receiving different treatment were performed. Mouse tumor models were constructed in A17fl/fl and A17α-MHCKO mice. In addition, cardiomyocyte-specific TRAF3-knockdown and TRAF3-overexpressing mice were generated. ADAM17 expression and activity were markedly upregulated in doxorubicin-treated mouse hearts and NRCMs. A17α-MHCKO mice showed less cardiomyocyte apoptosis induced by doxorubicin than A17fl/fl mice, and cardiomyocyte ADAM17 deficiency did not affect the anti-tumor effect of doxorubicin. In contrast, AAV9-oeA17 mice exhibited markedly aggravated cardiomyocyte apoptosis relative to AAV9-oeNC mice after doxorubicin treatment. Mechanistically, doxorubicin enhanced the expression of transcription factor C/EBPβ, leading to increased expression and activity of ADAM17 in cardiomyocyte, which enhanced TNF-α shedding and upregulated the expression of TRAF3. Increased TRAF3 promoted TAK1 autophosphorylation, resulting in activated MAPKs pathway and cardiomyocyte apoptosis. ADAM17 acted as a positive regulator of cardiomyocyte apoptosis and cardiac remodeling and dysfunction induced by doxorubicin by upregulating TRAF3/TAK1/MAPKs signaling. Thus, targeting ADAM17/TRAF3/TAK1/MAPKs signaling holds a promising potential for treating doxorubicin-induced cardiotoxicity.